Early Holocene thinning and final demise of the Scandinavian Ice Sheet across the main drainage divide of southern Norway - Romundset, Anders; Akçar, Naki; id_orcid:0 000-0002-5604-3179; Fredin, Ola; Andersen, Jane L.; Høgaas, Fredrik; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Yeşilyurt, Serdar; Schlüchter, Christian (Pergamon, 2023)
The thinning and final decay of the Scandinavian Ice Sheet in the Gudbrandsdalen area in central southern Norway is described, based on (1) cosmogenic 10Be surface exposure dating of 25 glacially transported boulders, (2) radiocarbon dating of plant remains in the basal strata in four lakes and (3) mapping of large ice-dammed lakes that formed at different elevations and at different times during the last deglacation. We complement the new chronology with previously published 10Be-ages from the same region. The dated samples are spread from mountain summits 1800 m a.s.l. to the valley floor at 250 m a.s.l. Our results suggest that the ice sheet surface remained well above 1800 m a.s.l. in northern Gudbrandsdalen throughout the Younger Dryas. During the Early Holocene the ice sheet thinned rapidly, at rates estimated to 1.7–5.8 m yr−1. The final phase of deglaciation involved formation of large ice-dammed lakes, most notably the Store Dølasjø which was formed after 10.4 ka BP and finally drained around 10.0 ka BP. The ice-marginal landforms that characterize the mountain region of northern Gudbrandsdalen, i.e., moraine ridges, lateral meltwater channels, as well as deposits and shorelines from ice-dammed lakes, thus collectively originate from a period of rapid ice sheet downwasting over ca. 1600 years. ISSN:0277-3791